Development and validation of a finite element model for road safety barrier impact tests. (June 2016) - Teng, Tso-Liang; Liang, Cho-Chung; Tran, Thanh-Tung
Road safety barriers are roadside structures installed on certain sections of the road to improve highway safety by preventing a vehicle from leaving the road and colliding with roadside hazards. Road safety barriers are an effective solution for reducing the risk of injuries on modern roads. A road safety barrier must meet minimum standards of construction and materials design. Normally, they must undergo crash tests according to the European standard EN 1317 or the Manual for Assessing Safety Hardware by the American Association of State Highway and Transportation Officials. On the basis of these standards, each safety barrier must pass standardized crash tests as mandated in their approval procedures. Currently, computer simulation methods are typically used by researchers to analyze the performance of roadside safety barriers. Advancement in computer technology could facilitate the finite element method in replacing expensive experimental tests. This paper presents an approach for constructing and evaluating a finite element model for road safety barriers according to European standard EN 1317 by using the finite element code LS-DYNA. Excellent agreement between real-world test data and simulation results was achieved for behavior and impact severity values. The results obtained using the model ensure the exactness of the proposed method and prove that the numerical method is a practical approach for eliminating road safety barrier problems. Furthermore, the model was able to replace experimental tests for developing road safety barriers, thus reducing time and money.